Receptor-Like Kinases BAK1 and SOBIR1 Are Required for Necrotizing Activity of a Novel Group of Sclerotinia sclerotiorum Necrosis-Inducing Effectors - Seifbarghi, Shirin; Borhan, Mohammad Hossein; Wei, Yangdou; Ma, Lisong; Coutu, Cathy; Bekkaoui, Diana; Hegedus, Dwayne D. (Frontiers in Plant Science, 2020)
Sclerotinia sclerotiorum is a characteristic necrotrophic plant pathogen and is dependent on the induction of host cell death for nutrient acquisition. To identify necrosis-inducing effectors, the genome of S. sclerotiorum was scanned for genes encoding small, secreted, cysteine-rich proteins. These potential effectors were tested for their ability to induce necrosis in Nicotiana benthamiana via Agrobacterium-mediated expression and for cellular localization in host cells. Six novel proteins were discovered, of which all but one required a signal peptide for export to the apoplast for necrotizing activity. Virus-induced gene silencing revealed that the five necrosis-inducing effectors with a requirement for secretion also required the plant co-receptor-like kinases Brassinosteroid Insensitive 1-Associated Receptor Kinase 1 (BAK1) and Suppressor of BAK1-Interacting Receptor-like Kinase 1 (SOBIR1) for the induction of necrosis. S. sclerotiorum necrosis-inducing effector 2 (SsNE2) represented a new class of necrosis-inducing proteins as orthologues were identified in several other phytopathogenic fungi that were also capable of inducing necrosis. Substitution of conserved cysteine residues with alanine reduced, but did not abolish, the necrotizing activity of SsNE2 and full-length protein was required for function as peptides spanning the entire protein were unable to induce necrosis. These results illustrate the importance of necrosis-inducing effectors for S. sclerotiorum virulence and the role of host extracellular receptor(s) in effector-triggered susceptibility to this pathogen.